2014
DOI: 10.1186/s40643-014-0008-6
|View full text |Cite
|
Sign up to set email alerts
|

Purification and partial characterization of serine alkaline metalloprotease from Bacillus brevis MWB-01

Abstract: Background: Proteases from bacteria are among the most important hydrolytic enzymes that have been studied due to their extracellular nature and high yield of production. Of these, alkaline proteases have potential for application in detergent, leather, food, and pharmaceutical industries. However, their usefulness in industry is limited by low activity and stability at high temperatures, extreme pH, presence of organic solvents and detergent ingredients. It is therefore very crucial to search for new alkaline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…It is reported that the activity of alkaline protease from Bacillus sp. and Bacillus megaterium RRM2 is increased by Ca 2+ ( Gupta et al., 2005 ; Rajkumar et al., 2011 ) and decreased by Hg 2+ , Zn 2+ and Co 2+ ( Venugopal and Saramma, 2007 ; Olajuyigbe and Falade, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the activity of alkaline protease from Bacillus sp. and Bacillus megaterium RRM2 is increased by Ca 2+ ( Gupta et al., 2005 ; Rajkumar et al., 2011 ) and decreased by Hg 2+ , Zn 2+ and Co 2+ ( Venugopal and Saramma, 2007 ; Olajuyigbe and Falade, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cross-linking in keratin fibers occurs through disulfide bonds, hydrogen bonds, and hydrophobic interactions. General proteases such as trypsin and pepsin cannot degrade keratin (Gupta and Ramnani 2006;Kreplak et al 2004;Olajuyigbe and Falade 2014).…”
Section: Introductionmentioning
confidence: 99%
“…PLI-1 from Indonesia's hot springs. In contrast, thermotolerant alkaline protease producing strain, Bacillus brevis MWB-01 was isolated from sub-soil from organic waste sites (Olajuyigbe and Falade, 2014). The members of the genus Bacillus are spore formers and also produce a number of biocidal metabolites/enzymes which makes them a common inhabitant of diverse extreme habitats (Nicholson et al, 2000).…”
Section: Here]mentioning
confidence: 99%
“…With the increasing emphasis on cost effectiveness for enzyme production, the use of low-cost fermentation medium and process optimization is of paramount importance for commercial gain. Recently, only a few studies investigated the protease producing potential of the Brevibacillus brevis ( Jaouadi et al, 2013 ;Olajuyigbe et al, 2014) but there is no previous report on process optimization using the design of experiment (DOE). In view of this, a statistical experimental design was employed to optimize culture conditions for higher alkaline protease using Brevibacillus brevis BT2 strain under submerged fermentation.…”
Section: Introductionmentioning
confidence: 99%